Analisis Penerapan Manajemen Sumber Daya Insani Di Koperasi Firdaus Berkah Bersama Kota Samarinda - Winarsih Winarsih; Bambang Iswanto; Angrum Pratiwi (Borneo Islamic Finance and Economics Journal, 2023)
Abstract The background of this research is that success in achieving company goals is a management achievement. Therefore in organizational activities, human resources have a major role. With the support of adequate infrastructure and facilities without the support of the role of human resources, the objectives of the Company's Vision and Mission will not be achieved properly. The term individual in human resources in Islam is known as Insani. For this reason, Human Resources in Islam are based on the concept that every employee is a human (not a machine) and not just a business resource. This research was conducted in order to find out how it is applied to human resource management in the Firdaus Berkah Bersama Cooperative, Samarinda City. and to find out how to implement the characteristics of the Prophet SAW in human resource management at the Firdaus Berkah Cooperative with the City of Samarinda. The type of research used in this research is descriptive research with a qualitative approach. This study uses primary data and secondary data by taking the data obtained in the form of interviews, observations and documentation, as well as obtaining data through journals or books that are used as reference materials. Data analysis techniques used include data reduction, data display (data presentation) and conclusions. The results of this study indicate that the Firdaus Berkah Bersama Cooperative of Samarinda City has implemented and practiced the function of Human Resource Management properly, honestly and trustworthy starting from the type of selection and recruitment with predetermined conditions and took several tests, one of which was the Koran. The training that is followed is in the form of seminars or webinars which are attended by the employees of the cooperative. The training aims to increase knowledge and expertise in their respective fields. The assessment is seen from the way of working, absenteeism, speed when completing work, providing financial compensation in the form of basic salary, bonuses, holiday allowances, BPJS fees, recreation costs and even Umrah costs, and the evaluation is carried out from daily, monthly then recaps to a year. Keywords: Management, Human Resources, Sharia Cooperative Abstrak Penelitian ini dilatar belakangi oleh Keberhasilan dalam mencapai tujuan perusahaan merupakan prestasi manajemen. Oleh sebab itu dalam kegiatan organisasi, sumber daya manusia mempunyai peranan utama. Dengan ditunjang prasarana dan sarana yang memadai tanpa didukung oleh peran sumber daya manusia maka tujuan Visi dan Misi Perusahaan tidak akan tercapai dengan baik. Istilah individu dalam sumber daya manusia dalam Islam dikenal dengan istilah Insani. Untuk itu Sumber Daya Insani dalam Islam yang didasarkan pada konsep bahwa setiap karyawan adalah manusia (bukan mesin) dan bukan hanya sumber daya bisnis. Penelitian ini dilakukan guna untuk Mengetahui Bagaimana Penerapan pada Manajemen Sumber Daya Insani di Koperasi Firdaus Berkah Bersama Kota Samarinda. dan untuk Mengetahui Bagaimana Implementasi Sifat-sifat Nabi SAW pada Manajemen Sumber Daya Insani di Koperasi Firdaus Berkah Bersama Kota Samarinda. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Penelitian ini menggunakan data primer dan data skunder dengan cara pengambilan data yang didapat berupa wawancara, observasi dan dokumentasi, serta memperoleh data melalui jurnal atau buku yang dijadikan sebagai bahan referensi. Teknik analisis data yang digunakan meliputi redukasi data, display data (penyajian data) dan kesimpulan. Hasil penelitian ini menunjukkan bahwa Koperasi Firdaus Berkah Bersama Kota Samarinda telah menerapkan dan mempraktikkan fungsi Manajemen Sumber daya insani dengan baik, jujur dan amanah mulai dari jenis seleksi dan perekrutan dengan syarat-syarat yang telah ditentukan dan mengikuti beberapa tes salah satunya mengaji. Pelatihan yang diikuti berupa seminar atau webinar yang diikuti oleh para karyawan koperasi tersebut. dilakukan pelatihan bertujuan untuk menambah pengetahuan dan keahlian dibidangnya masing-masing. Penilaian dilihat dari cara bekerja, absensi, kecepatan saat menyelesaikan kerja, pemberian kompensasi finansial berupa gaji pokok, bonus, tunjangan hari raya, biaya BPJS, biaya rekreasi bahkan biaya Umroh, dan Evaluasi dilakukan dari harian, bulanan kemudian direkap menjadi setahun. Kata Kunci : Manajemen, Sumber Daya Insani, Koperasi Syariah